1984
DOI: 10.1111/j.1365-2621.1984.tb13184.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thixotropic Behavior of Soft Cheeses

Abstract: Time-dependent structural decay (h) of four different spreadable cheeses was established using a Wells-Brookfield cone and plate viscometer. The h values were determined at constant values of shear rate, (10 set-l to 200 set-'). The products studied were two samples of commercial Neufchatel cheese (one plain and one chocolate flavored) and two different saqples of cheese prepared using the Maubois, Mocquot and Vassal (MMV) method, which utilizes milk concentrated by ultrafiltration. All samples presented a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 2 publications
3
6
0
Order By: Relevance
“…3). Massaguer-Roig et al (1984) reported similar results on Neufchatel and cream cheeses by recording a decrease of shear stress with time of shear (at constant shear rate). The DCC Ϫ flow curve was typical of foods such as mayonnaise, heavy cream, spread and shortening, with a 'static yield value' ( 1 ) in the up curve (from 0 to 300 s Ϫ1 shear rate) indicating the presence of a 3-dimensional network (Martin et al, 1964;Barry and Warburton, 1968;Davis, 1973).…”
Section: Flow Curves After Storage Of DCC Cooled To 20њcsupporting
confidence: 57%
“…3). Massaguer-Roig et al (1984) reported similar results on Neufchatel and cream cheeses by recording a decrease of shear stress with time of shear (at constant shear rate). The DCC Ϫ flow curve was typical of foods such as mayonnaise, heavy cream, spread and shortening, with a 'static yield value' ( 1 ) in the up curve (from 0 to 300 s Ϫ1 shear rate) indicating the presence of a 3-dimensional network (Martin et al, 1964;Barry and Warburton, 1968;Davis, 1973).…”
Section: Flow Curves After Storage Of DCC Cooled To 20њcsupporting
confidence: 57%
“…Comparing the results of experiments at constant shear stress with other published results at constant shear rate (Tiu and Boger 1974;Massaguer et al 1984;Ford and Steffe 1986), the relationships obtained (13,14,15,16) describing dependence of A to r , are similar. Values of kb2 and Xe are in the same range of values found by these authors with mayonnaise, starch thickened strained apricots and soft cheeses.…”
Section: Discussionsupporting
confidence: 78%
“…Knowledge of product flow properties is important for its development, quality control, consumer acceptability, processing design and control, as has been thoroughly discussed by several authors. However, an equation which can be used to effectively describe thixtropic behaviour has not yet been established (Mewis 1979;Figoni and Shoemaker 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the yield stress measured (between 7 k-I Pa and 2 f 1 Pa) compared with published literature, values according to inagaki (1986) the yield stress values extrapolated from the up and down curves at 20C vary from 1 Pa to 14 Pa depending on the brand and the lowest values are obtained from the down flow curves. Nishijima and Inagaki (1987) observed no temperature dependency for the extrapolated yield stress from the down curves. Extrapolating a yield value from experiments with decreasing shear rate could be considered valid when no buildup occurred and more generally when the thixotropic behaviour was removed by previous increasing the shear rate procedure.…”
Section: Modelling the Time-dependency In The Commercial Stirred Yoghmentioning
confidence: 95%
“…(7), qi is the apparent viscosity at the beginning of shearing, the yield stress at equilibrium, n the flow behaviour index and ke the consistency index at equilibrium. This structural model was applied to various foodstuffs: Tiu and Boger (1974) applied it to mayonnaise, Massaguer-Roig et al (1984) to different varieties of melted cheese and Martinez-Padilla and Hardy (1989) to Bechamel sauce. In each of these studies 2 gave a good fit for p in Eq.…”
Section: Introductionmentioning
confidence: 99%